A Glucose/Oxygen‐Exhausting Nanoreactor for Starvation‐ and Hypoxia‐Activated Sustainable and Cascade Chemo‐Chemodynamic Therapy. Issue 31 (15th June 2020) - Guo, Yuxin; Jia, Hao‐Ran; Zhang, Xiaodong; Zhang, Xinping; Sun, Qing; Wang, Shao‐Zhe; Zhao, Jing; Wu, Fu‐Gen
Abstract: Fenton reaction‐mediated chemodynamic therapy (CDT) can kill cancer cells via the conversion of H2 O2 to highly toxic HO. However, problems such as insufficient H2 O2 levels in the tumor tissue and low Fenton reaction efficiency severely limit the performance of CDT. Here, the prodrug tirapazamine (TPZ)‐loaded human serum albumin (HSA)–glucose oxidase (GOx) mixture is prepared and modified with a metal–polyphenol network composed of ferric ions (Fe 3+ ) and tannic acid (TA), to obtain a self‐amplified nanoreactor termed HSA–GOx–TPZ–Fe 3+ –TA (HGTFT) for sustainable and cascade cancer therapy with exogenous H2 O2 production and TA‐accelerated Fe 3+ /Fe 2+ conversion. The HGTFT nanoreactor can efficiently convert oxygen into HO for CDT, consume glucose for starvation therapy, and provide a hypoxic environment for TPZ radical‐mediated chemotherapy. Besides, it is revealed that the nanoreactor can significantly elevate the intracellular reactive oxygen species content and hypoxia level, decrease the intracellular glutathione content, and release metal ions in the tumors for metal ion interference therapy (also termed "ion‐interference therapy" or "metal ion therapy"). Further, the nanoreactor can also increase the tumor's hypoxia level and efficiently inhibit tumor growth. It is believed that this tumor microenvironment‐regulable nanoreactor with sustainable and cascade anticancer performance and excellent biosafety represents an advance in nanomedicine. Abstract : A self‐amplified nanoreactor termed HSA–GOx–TPZ–Fe 3+ –TA (HGTFT), consisting of human serum albumin, glucose oxidase, tirapazamine (TPZ), Fe 3+, and tannic acid (TA), is prepared for sustainable and cascade cancer therapy with exogenous H2 O2 production and TA‐accelerated Fe 3+ /Fe 2+ conversion. The nanoreactor can convert oxygen into HO for chemodynamic therapy, consume glucose for starvation therapy, and provide a hypoxic environment for TPZ radical‐mediated chemotherapy.